CHOOSING CORRECT MATERIALS FOR READING ACTIVITIES (Conferencea, 2022)
The point of the current paper is to illustrate some difficulties to choose correct reading materials for language learners. Moreover, it discusses some ideas about learning styles and teaching strategies as learning styles are crucial for the process of learning.